การเปรียบเทียบพฤติกรรมและความสามารถของนักลงทุนในตลาดหลักทรัพย์แห่งประเทศไทย - จิรัฏฐ์ บริบูรณ์ธนกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To compare the behaviors and explore the performance of different groups of investors; foreign, institutional and individual investors, in the Stock Exchange of Thailand (SET). In this research, the vector auto regressive (VAR) model is employed to uncover the patterns of investment behavior, and the elasticity model together with covariance model are utilized to assess the investment performance, by using data collected from the Stock Exchange of Thailand (SET) between January 1995 and December 2003. The result of VAR model shows that foreign and institutional investors tend to invest according to their historical activities but it is not the case for individual investors. In addition, foreign investors are likely to invest as opposed to individual and institutional investors whereas individual investors tend to follow institutional investors but there re oppose to foreign investors. However, institutional investors, in early stage, tend to follow individual investors but there re oppose to foreign investors. However, as the time passed the pattern of investment is turned upside down. In terms of investment performance, this study takes into account 2 aspects: cost of investment and timing of investment. The cost of investment comprises the cost, of buying and selling securities. The finding shows that foreign investors bear the highest cost of selling at all times. For institutional and individual investors, the finding reveals 2 divert views. During the first month, the cost of selling for individual investors is the lowest but after that individual investors tend to bear, higher cost than institutional investors. On the other hand, for the cost of buying, the findings show 2 divert views. During the first week, institutional investors bear the lowest cost, followed by foreign and individual investors respectively. But after that period foreign investors bear the lowest cost of buying followed by individual and institutional investors respectively. Furthermore, in terms of investment timing, the finding points out that during the first month, the investment timing of institutional investors is the best followed by foreign investors and individual investors respectively. However, after the period, foreign investors tend to have the best timing, followed by individual investors and institutional investors respectively.